Overlap and integration between the competent anti-corruption bodies and other regulatory bodies - Attiya, Ali; Naser, Alaa (Journal of Legal Sciences, 2022)
The protection of public money and its surrounding with special provisions that guarantee that protection from every legal or material assault by the supervisory bodies competent to combat corruption are described as a criminal procedural protection aimed at prosecuting criminals in general crimes and government corruption crimes in particular, and working to recover funds and return them to the state treasury, These agencies operate in an integrated format, each other and in a coherent manner with each other, in order to achieve the purpose of their establishment and reach the basic goal, which is to eliminate corruption from the theoretical side Practical reality.